Higher Education System In An India - S. Santhana Jeyalakshmi (AG Volumes, 2022)
The world has come to understand that the quality of a country’s educational system has a direct impact on its economic performance. A nation’s power is built on its education. Every sophisticated economy has a well-educated citizenry as a given. Only China and the United States have better higher education systems than India. India has achieved consistent progress in education since its independence. The higher education system in India has encountered many challenges, but it also offers many opportunities to overcome these challenges and improve the system. College and university transparency and responsibility are essential components of the answer, as well as fresh scientific research into how people learn. Our economy can only grow if we have a well-educated and well-skilled workforce. So it’s quite simple for us to leap from being an underdeveloped economy into one that’s a well-developed Nation. An important part of attracting meritorious students to study and conduct research in India rather than going abroad is to overcome the main challenges, such as a lack of practical experience while studying non-science topics, a lack of attractive salary packages, a failure to identify student dignity, and a lack of adequate facilities in rural and backward areas that are lacking. The only way to end this is to provide merit-based scholarships and to provide jobs with competitive salaries to those who qualify for them.